2017
DOI: 10.1002/pts.2283
|View full text |Cite
|
Sign up to set email alerts
|

Long‐time Performance of Bottles Made of PET Blended with Various Concentrations of Oxygen Scavenger Additive Stored at Different Temperatures

Abstract: Blending of poly(ethylene terephthalate) (PET) with oxygen scavenger additives is a way to reduce ingress of oxygen into PET bottles made of these blends. The objective is to reduce oxidation of packaged beverages and oils. However, few studies were performed about the long-time influence of temperature on PET bottles with oxygen scavenger additives. Such knowledge is relevant for the development of accelerated tests. In this study, the influence of temperature on oxygen permeation of PET bottles with the oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Common applications include sachets containing the scavenger in powder form that are added to a package and also packaging films (monolayer or multilayer) incorporating the scavenger (Singh et al, 2011 ; Realini and Marcos, 2014 ). Many commercial O 2 scavengers are based on iron, sulfite, or oxidizable polymers and they have been in use since the 1990s (Rooney, 2005 ; Saengerlaub and Mueller, 2017 ). Besides these established systems, the application of polyphenols as O 2 scavengers has gained attention due to their availability from renewable resources and their high O 2 absorption capacity (Wanner, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Common applications include sachets containing the scavenger in powder form that are added to a package and also packaging films (monolayer or multilayer) incorporating the scavenger (Singh et al, 2011 ; Realini and Marcos, 2014 ). Many commercial O 2 scavengers are based on iron, sulfite, or oxidizable polymers and they have been in use since the 1990s (Rooney, 2005 ; Saengerlaub and Mueller, 2017 ). Besides these established systems, the application of polyphenols as O 2 scavengers has gained attention due to their availability from renewable resources and their high O 2 absorption capacity (Wanner, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 8 shows the results of chemical inertia of the samples. The analysis carried out showed a strong sensitivity of all formulations to the aqueous solution containing NaOH (pH [13][14]. This solution is strongly basic.…”
Section: Resultsmentioning
confidence: 99%
“…PET can also be modified by blending or by the addition of oxygen scavengers or coated to improve its barrier properties (. [7][8][9][10][11][12][13][14][15][16] Oxygen barrier as such low as~0.2 cc/cm m À2 atm À1 day À1 can be achieved on PET bottle. However, PET requires accurate drying before being processed and processing temperature very high that seldom is lower than 250 C in injection molding of preforms.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the poly(m-xylene adipamide) MXD6, an efficient oxygen scavenger additive, which acts as passive polymer barrier reducing the oxygen permeation in the PET bottles used for the packaging of beverages and oils [54,55], could be used as AA. However, some authors [21,56] reported that the MXD6 layer can generate non-intentionally added substances (NIAS) in the PET bottles.…”
Section: Studies On Potential Functional Aldehydes Scavangersmentioning
confidence: 99%